(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To develop and validate a book on the management of incontinence-associated dermatitis in newborns, children, adults, and older adults. Method: A descriptive, exploratory study. The chapters of the book were defined after a search for studies published since 2009 in the PubMed/Medline, LILACS, BDENF, and EMBASE databases, using the keywords: adult, child, dermatitis, diaper rash, urinary incontinence, fecal incontinence, and aged. The written content and illustrations were then created. Upon completion, the book was validated by experts through the Delphi technique and the content validity index was calculated. Results: Based on the literature review, the book’s chapters were defined, and the textual content was written and proofread to improve grammar and readability. The illustrations were then included and the book layout was designed. The book was validated by seven experts in two rounds of consultation, achieving a 96% level of agreement among them. Conclusion: The book on Management of Incontinence-Associated Dermatitis in newborns, children, adults, and older adults was successfully developed and validated.